2020
DOI: 10.3390/nu12113541
|View full text |Cite
|
Sign up to set email alerts
|

Association among Vitamin D, Retinoic Acid-Related Orphan Receptors, and Vitamin D Hydroxyderivatives in Ovarian Cancer

Abstract: Vitamin D and its derivatives, acting via the vitamin D receptor (VDR) and retinoic acid-related orphan receptors γ and α (RORγ and RORα), show anticancer properties. Since pathological conditions are characterized by disturbances in the expression of these receptors, in this study, we investigated their expression in ovarian cancers (OCs), as well as explored the phenotypic effects of vitamin D hydroxyderivatives and RORγ/α agonists on OC cells. The VDR and RORγ showed both a nuclear and a cytoplasmic locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Importantly, recent experimental studies have shown that knocking out of the VDR in melanoma cells increase their malignant behavior and decreases responsiveness to active form of vitamin D indicating that the VDR can serve as the melanoma tumor suppressor gene (69), which is consistent with the role of the VDR as the tumor suppressor gene in the skin as originally proposed by Bikle (44). Of note, defects in VDR lead to increased malignant behavior in other tumors including bladder, ovarian, lung and breast cancers, lymphomas (70)(71)(72)(73)(74)(75).…”
Section: Vdr Expression As a Prognostic Biomarkersupporting
confidence: 76%
“…Importantly, recent experimental studies have shown that knocking out of the VDR in melanoma cells increase their malignant behavior and decreases responsiveness to active form of vitamin D indicating that the VDR can serve as the melanoma tumor suppressor gene (69), which is consistent with the role of the VDR as the tumor suppressor gene in the skin as originally proposed by Bikle (44). Of note, defects in VDR lead to increased malignant behavior in other tumors including bladder, ovarian, lung and breast cancers, lymphomas (70)(71)(72)(73)(74)(75).…”
Section: Vdr Expression As a Prognostic Biomarkersupporting
confidence: 76%
“…The VDR is implicated in the regulation of an array of biological activities, including development and progression of cancer, for example breast, prostate and ovarian cancers and melanoma [53][54][55]. Brozyna et al [31,46] showed that less advanced tumors exhibited significantly higher VDR expression than those in the advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…In negative controls, the primary antibodies were omitted and replaced with antibody diluent. The sections were evaluated semi-quantitatively, as previously described [ 43 , 44 ]. Since we observed heterogenous: agranular and granular staining, the assessment was performed separately for each staining pattern.…”
Section: Methodsmentioning
confidence: 99%